Application Of Project Scheduling Towards Multiple Cropping Process To Achieve Maximum Land Optimization In PT. XYZ - Amani, Salma; Handayati, Yuanita (Journal of Business and Management, 2019)
According to the global economy, On 2017, Badan Pusat Statistik stated that, the consumption of fruit and vegetables until 2016, showed that almost all of Indonesian citizen which is 97,29 percent of them consumed vegetables.PT. XYZ seen this situation as their opportunities to run their business activities. The company are planning to produce agricultural product such as vegetables, specifically carrot. To stabilize the harvesting process, PT. XYZ will applied multiple crop rotation method. The company decide the supporting plants will be sweet corn and scallion. To develop and present an optimization model of production planning, project scheduling will applied as the tool to demonstrate the production planning.Construct schedule in production planning, developing linear programming is needed to create the mathematical model. Before build the model, several data that related to the model require to be gathered. According to Darst (1990), there are three components involved to formulate linear programming into a model, which are specify the decision variables, constraints and the objective function. Subsequently the completed model can be running in software named MATLAB. The result from processing in MATLAB, shows the amount of required land and the pattern of rotation so the company could meet the weekly demand of each commodities for time period 52 weeks. From the final result, it can concluded that PT. XYZ need 1,893 ha so the company could fulfil the weekly demand of each commodities and so the rotation system could be performed based on principle of rotation system For more specifically 60 plotting area with each area has sizes for ±315 m2 are needed to utilized.Keywords: Agriculture, multiple cropping rotation, optimisation method, scheduling, linear programming, mathematical model, gantt chart"